Enhancement of ADP-Induced Platelet Aggregation by Exercise Test in Coronary Patients and Its Prevention by Pyridinolcarbamate - Yamazaki, H; Kobayashi, I; Shimamoto, T (Thrombosis and Haemostasis, 1970)
ADP-induced platelet aggregation in citrated platelet rich plasma (CPRP) was examined using a photoelectric system. To exclude a variation in intensities of platelet aggregation in repeated measurements and to compare intensities of different samples, the maximum deflection of the optical density of CPRP induced by adding ADP solution was divided by a deflection of the optical density of the platelet free plasma and its value, shown as a percentage, was defined as an intensity of ADP-induced platelet aggregation. In this method, the linearity was found in the dose response curve of the platelet aggregation induced by 10−6, 3 × 10−6 and 10−5 molar of ADP with statistical significance. These variation coefficients were less than 5% in the responses induced by the higher doses of ADP. Changes in the ADP-induced platelet aggregation after a Master’s two step test were examined in 13 patients with angina pectoris 3 h after oral administration of placebo or 1 g of pyridinolcarbamate. Under placebo pretreatment, an enhancement of platelet aggregation was observed 1 min after the exercise test with statistical significance (P < 0.01 ∼ 0.05). In the cases of the same subjects pretreated with pyridinolcarbamate, such change was not observed at any time. Using a parallel line assay, an inhibitory effect of pyridinolcarbamate against enhancement of ADP-induced platelet aggregation after the exercise was also recognized with statistical significance (P < 0.01). In the 10 healthy volunteers, there was no statistically significant enhancement of ADP-induced platelet aggregation using any concentration of ADP 1 to 10 min after the exercise test.